Report of the External Review Committee on IMF-World Bank Collaboration. (Policy Papers; Policy Paper ;, 2007)
The Bank and Fund are the only two international financial institutions with near universal membership. They have an important role to play in providing global public goods and in helping countries obtain the benefits of globalization, as well as handle the pressures it creates. While the Bank and Fund have separate mandates, they are inherently linked and close collaboration is vital. Indeed, the costs to members of poor collaboration would be significant. Although there are many examples of good collaboration and there have been clear improvements over the years, there is scope for further improvements in the view of the Committee.